2021
DOI: 10.7554/elife.66275
|View full text |Cite
|
Sign up to set email alerts
|

A bone-specific adipogenesis pathway in fat-free mice defines key origins and adaptations of bone marrow adipocytes with age and disease

Abstract: Bone marrow adipocytes accumulate with age and in diverse disease states. However, their origins and adaptations in these conditions remain unclear, impairing our understanding of their context-specific endocrine functions and relationship with surrounding tissues. In this study, by analyzing bone and adipose tissues in the lipodystrophic 'fat-free' mouse, we define a novel, secondary adipogenesis pathway that relies on the recruitment of adiponectin-negative stromal progenitors. This pathway is unique to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Adipoq-Cre recombination in the mouse skeleton occurs in marrow adipocytes, in a network of stromal cells residing among hematopoietic cells and around blood vessels, and in cells lining the trabecular bone surfaces. 11 , 13 15 Adq -marrow stromal cells were reported to coincide with a fraction of Lepr-Cre- targeted stromal cells 13 and to largely overlap with the PDGFRβ + /VCAM-1 + /CXCL12 + (CAR) stromal cell subsets. 14 In addition, it was shown that the majority of Adq -marrow stromal/perivascular cells are post-natal adipocyte progenitors, named MALPs, that support marrow vasculature and are involved in the regulation of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Adipoq-Cre recombination in the mouse skeleton occurs in marrow adipocytes, in a network of stromal cells residing among hematopoietic cells and around blood vessels, and in cells lining the trabecular bone surfaces. 11 , 13 15 Adq -marrow stromal cells were reported to coincide with a fraction of Lepr-Cre- targeted stromal cells 13 and to largely overlap with the PDGFRβ + /VCAM-1 + /CXCL12 + (CAR) stromal cell subsets. 14 In addition, it was shown that the majority of Adq -marrow stromal/perivascular cells are post-natal adipocyte progenitors, named MALPs, that support marrow vasculature and are involved in the regulation of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…(C) Adiponectinprogenitors are predominantly of the osteogenic lineage, but are also able to differentiate into BMAs in metabolic disorders or in aging adults. This population elicits similar properties as cBMAs (30). BMSC, bone mesenchymal stem cells; rBMA, regulated bone marrow adipocyte; cBMA, constitutive bone marrow adipocyte; MALP, marrow adipogenic lineage precursor; C/EBP, CCAAT/enhancer-binding protein; FA, fatty acid; PPARg, peroxisome proliferator-activated receptor gamma.…”
Section: Originmentioning
confidence: 99%
“…This population was able to differentiate into ectopic BMAs with age and metabolic diseases. These BMAs have increased lipid storage and are not thermogenic as they are unresponsive to cold stress or β3-adrenergic stimulation ( 30 ). Despite that adiponectin is an essential adipocyte specific cytokine, the discovery of adiponectin-independent BMA subsets allows to speculate that further origins of BMAs remain to be revealed.…”
Section: Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, TCM uses both interior therapies in conjunction to external therapy. TCM considers 3 phases when it comes to bone deformities: 1) during first phase, there is harm to the blood vessels due to stagnation of “qi” and blood, and also obstructed meninges, which together leads to pain; 2) in the second phase, the inflammation eventually subsides and the pain is significantly reduced, but the bruises remain, and connective tissues are not repaired; 3) in the third phase, the overall bone damage has now been healed, but remedy to pacify and improve bone regeneration, and improve the internal environment is yet required ( Tang et al, 2021 ; Zhang et al, 2021 ). Icariin (ICA) being a traditional Chinese medicine which was found to repair the vascular system and successfully modulate intracellular senescence in bones.…”
Section: Traditional Chinese Medicines In Osteoporosis and Bone Regen...mentioning
confidence: 99%